A Study on Bio- Medical Waste Management Using Kayakalp Tool at District Hospital in Southern India - Somaiah, Parvathy T; Shivaraj B M (National Journal of Community Medicine, 2016)
Background: As a part of the Swachh Bharat Abhiyaan campaign, the Ministry of Health and Family welfare launched “Kayakalp”, an initiative to promote cleanliness and enhance the quality of public health facilities. This study was conducted to assess performance of Biomedical Waste management in Government District hospital using the Kayakalp assessment tool. Material and methods: A cross sectional observational study was conducted by using the Kayakalp assessment tool. Direct observation, Staff interview and documents review were the methods used. Results: The assessment using the tool showed Segregation of medical waste(80%), Collection and transport (50%), Sharp management(90%), Storage of waste( 50%), Disposal(60%), management of Hazardous waste( 70%), Solid waste management(50%), Liquid Waste management( 60%), Institutional equipment and supplies for waste management( 60%) and Statutory Compliances (80%). The biomedical waste management of healthcare setting is about 57%. Conclusion: Improvements in Biomedical waste management can be made by increasing the knowledge, awareness and practices among the healthcare workers by providing mandatory training.